Rezension von: Rombold, Bernd, 150 Jahre Schützengilde Backnang 1848 e. V. - Trefz, Bernhard (Backnanger Jahrbuch, 1998)
150 Jahre Schützengilde Backnang 1848 e.V. Verantwortlich Bernd Rombold. O. O. o. J. (1998), 64 ungez. S.